Innovation of Assessment Techniques on Mahārah Kitābah in Arabic Textbooks Based on Higher-Order Thinking Skills (HOTS) - Fitria, Nurmala; Baroroh, R Umi (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This study aims to discover the innovative writing skills assessment techniques in class X Arabic books published by the Ministry of Religion in 2020 based on HOTS (Higher Order Thinking Skills). This research is library research, and this research is descriptive qualitative literature research. The Grade X Arabic book published by the Ministry of Religion in 2020 is the primary source of information for this essay, which is also supported by other written sources such as books, periodicals, etc. Referring KMA (Keputusan Menteri Agama) is a Decree of the Minister of Religion Number 183 of 2019; it is explained that all types and assessment techniques must be directed at measuring the attainment of higher-order thinking skills or HOTS. This class X Arabic book published by the Ministry of Religion in 2020 is an implementation of KMA (Keputusan Menteri Agama), is Decree of the Minister of Religion Number 183 of 2019. After a more in-depth analysis, the results of this study show that the technique of assessing aspects of knowledge in writing techniques or mahārah kitābah in class X Arabic books published by the ministry religion 2020 does not entirely refer to HOTS, there are still some of the questions that are still under the HOTS category.